PENGARUH KUALITAS AUDIT, UKURAN KAP, DAN AUDIT DELAY TERHADAP PERGANTIAN AUDITOR DENGAN KOMITE AUDIT SEBAGAI VARIABEL MODERASI - Octavia Dewi; Hermi Hermi (STMIK Widuri Jakarta, 2026)
This study aims to analyze the effect of audit quality, audit firm size, and audit delay on auditor switching with the audit committee as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange during the 2016–2021 period. This study used a quantitative approach with purposive sampling method. The sample consisted of 28 manufacturing companies with a total of 168 observations. Data analysis was conducted using logistic regression analysis. The results indicate that audit quality and audit firm size have a positive effect on auditor switching, while audit delay has a negative effect on auditor switching. The audit committee strengthens the effect of audit firm size on auditor switching and weakens the effect of audit delay on auditor switching. However, the audit committee is unable to moderate the effect of audit quality on auditor switching.